High-Performance Sensorless Operation of Motor-Generator Set With an Improved Torque-Ripple Minimization Strategy - Hussien, Mohamed G.; Salem Elbarbary, Zakaria M.; Hassan, Abd El-Wahab (Frontiers in Energy Research, 2022)
This paper aims at minimizing the torque ripples using variable switching frequency technique of PWM (VSFPWM) of the surface-mounted permanent magnet synchronous motor (SPMSM) for a high-performance operation of a motor-generator set. The proposed system was employed to drive the promising brushless doubly-fed reluctance generator (BDFRG) with a sensorless vector-control topology. Validity of the rotor-position/speed estimation critically affects most of the sensorless control strategies. Therefore, a simple estimation method is proposed for the positioning of rotor of the generator. The presented control strategies are confirmed with some of the obtained results to assure its controllability.